Parental presence during invasive pediatric procedures: what does it depend on? - Laura Palomares González; Iván Hernández Caravaca; Carmen Isabel Gómez García; Manuel Sánchez-Solís de Querol (Universidade de São Paulo, 2023)
Abstract Objective: family-centered care during invasive procedures has been endorsed by many professional health care organizations. The aim of this study was to evaluate the health professionals' attitudes towards parental presence during their child's invasive procedure. Method: pediatric healthcare providers (divided in professional categories and range of ages) from one of the Spain's largest hospitals were asked to complete a questionnaire and write free-text comments. Results: 227 responded the survey. Most (72%) participants, in their answers, reported that parents are sometimes present during interventions, although there were differences between professional categories in this respect. The procedures in which the parents were present were those considered "less invasive" (96% of cases), while only 4% were present in those considered "more invasive". The older the professional, the less necessary parental presence was considered. Conclusion: the attitudes towards parental presence during pediatric invasive procedure are influenced by the professional category, the age of the healthcare provider and the invasiveness of the procedure.